Vidas desperdiçadas? Uma análise de Estamira, de Marcos Prado, e No quarto de Vanda, de Pedro Costa - Mônica Horta Azeredo (Estudos de Literatura Brasileira Contemporânea)
Vanda and Estamira would only be taken as ordinary women placed in under- privileged social universes and on the brink of extinction. However, when hoisted by the hands of filmmakers, they are transformed into characters of their own and make room for something that has always been historically denied to them: the speech. While approaching the realistic to the represented, these docu-fictions are an invitation to ponder over what Bauman defines as “wasted lives”. By making use of a cinematographic language contrary to the ones of the canons, the film- makers Pedro Costa and Marcos Prado contribute to, by means of a rare snip, an identitary and partial construction of the Portuguese and Brazilian society. Despite of the substantial temporal-spatial distance between these two women, the comparison of the works of art is something possible and high-yielding.